ANALISIS KUALITAS INTRUSI ANDESIT SEBAGAI BAHAN BANGUNAN BERDASARKAN SIFAT KETEKNIKAN DI DAERAH BEJI, KECAMATAN UNGARAN TIMUR, KABUPATEN SEMARANG, JAWA TENGAH - Retongga, Nofrohu; Purnamawati, Dwi Indah; Rakhman, Arie Noor (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2021)
This study aims to identify the quality of andesite intrusive rocks as a building material. The research location is in the Beji area, East Ungaran District, Semarang Regency, Central Java Province. Analysis of rock quality using data from the test results of engineering and petrographic properties. The andesite studied is an intrusion into basalt. Based on the quality standard requirements for natural stone for buildings (SNI 03-0394-1989) these rocks can be mined for building materials, especially medium to heavy building foundations (1,150.040 -1,421.621 kg/cm2). The middle andesite has a higher strength than the lower andesite. The strength of the rock is supported by resistant minerals in the form of plagioclase, which dominates up to 35%. However, in the andesite body getting down, olivine tends to decrease by 5%. The weathering of these minerals is influenced by the condition of the water in the rock where the water content is 0.391 to 0.412%. In water-saturated conditions, the degree of saturation of the lower rock can reach 100%, exceeding the rock above, 87.5%. The strength of the rock at the bottom is lower, making the slope potentially easy to collapse when the mining method is started from the bottom, especially the excavation is carried out on steep vertical slopes.